Advanced Biofuels and Beyond: Chemistry Solutions for Propulsion and Production. Issue 20 (21st April 2017) - Leitner, Walter; Klankermayer, Jürgen; Pischinger, Stefan; Pitsch, Heinz; Kohse‐Höinghaus, Katharina
Abstract: Sustainably produced biofuels, especially when they are derived from lignocellulosic biomass, are being discussed intensively for future ground transportation. Traditionally, research activities focus on the synthesis process, while leaving their combustion properties to be evaluated by a different community. This Review adopts an integrative view of engine combustion and fuel synthesis, focusing on chemical aspects as the common denominator. It will be demonstrated that a fundamental understanding of the combustion process can be instrumental to derive design criteria for the molecular structure of fuel candidates, which can then be targets for the analysis of synthetic pathways and the development of catalytic production routes. With such an integrative approach to fuel design, it will be possible to improve systematically the entire system, spanning biomass feedstock, conversion process, fuel, engine, and pollutants with a view to improve the carbon footprint, increase efficiency, and reduce emissions. Abstract : Take on fuel : The design of future engine fuels with reduced carbon footprints and low emissions requires in‐depth chemical knowledge of the complete value chain—from the feedstock to the propulsion system. Linking combustion chemistry with fuel production strategies is key for the development of advanced biofuels that can contribute to sustainable and clean mobility and road transportation.